(untitled) (Annals of Medical Research, 2023)
Aim: The aim was to evaluate the clinical and laboratory characteristics of children with Wilson’s disease (WD) with and without neurological presentation with abnormalities on brain magnetic resonance imaging (MRI) and to describe the relationship of these observations with disease severity and functional outcome and their impact on prognosis. Materials and Methods: Demographic, neuropsychiatric findings, laboratory, disease severity and functional results of 48 children with neurologically symptomatic and asymptomatic WD were evaluated retrospectively. Results: A significant positive correlation was found between the neurologic symptom score and functional outcome in WD with neurological presentation (p <0.001). A significant positive correlation was found between disease severity scores (PELD, MELD, Child Pugh and Dhwin score) and modified Rankin scores (mRS) in WD without neurological presentation (p <0.001, 0.004, <0.001, 0.001, respectively). In addition, a significant positive correlation was found between total bilirubin, direct bilirubin and International Normalized Ratio (INR) values ​​and mRS scores (p= 0.006, 0.012, 0.004, respectively). Kayser-Fleischer Ring sign in the eye was higher in the group with neurological symtomatic WD (p <0.001). The number of patients presenting with clinic of fulminant hepatitis and hepatic encephalopathy was significantly higher in the neurological asymptomatic group (p <0.001). Conclusion: Brain MRI changes may occur even in hepatic WD and presymptomatic cases, although infrequently, regardless of the presence of neurological symptoms. It should be known that neurological symptoms in children and adolescents may occur without significant liver disease. Even without neurological symptoms, all children with WD should have a brain MRI before treatment.